Tren Global dan Lokal dalam Penurunan Stunting: Analisis Bibliometrik dari Studi Terpilih - Pasli, Imam (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2024)
Stunting is a serious public health problem with high prevalence in developing countries, including Indonesia, which has a significant impact on child development. This study aims to analyze global and local trends in stunting reduction, by identifying factors that influence the effectiveness of policies and programs in reducing stunting prevalence. Bibliometric analysis methods were used to review and evaluate relevant literature, identifying successes and challenges in implementing stunting interventions. The findings suggest that effective management of stunting requires a multi-sectoral approach involving health, nutrition, sanitation, and education. The analysis emphasizes the importance of coordinated policies and specifically designed intervention programs, as well as community engagement. This study provides important insights for policymakers and health practitioners in designing more effective strategies to address stunting in the future.